Participation in suicide and euthanasia. Outline of the penal treatment in Spain (2012)
This writing takes as matter the regulation in the Spanish law about behaviors, such as the inducement or assistance to suicide, form one side, and the euthanasia, from the other one. It is expressed how the Spanish regulation in this matter is poor and f